VOLLEYBALL TEAM SPORTS IN STUDENT COOPERATION TEACHING TO SUCCESS - Madaminov Oribdjan Nishanbayevich (Proximus Journal Publishing, 2025)
The higher state educational standard requires students to be a specialist in the field of physical culture (bachelor) with knowledge and socio-economic sciences: understanding the role of physical culture in human development and professional training; to have a system of practical skills and abilities that ensure preservation and strengthening of health, development and improvement of psychophysical abilities, qualities, self-determination in physical culture; it should include features such as gaining experience to achieve life and professional goals
Keywords: Volleyball; Taem sports; Student cooperation